A combination of single-drop microextraction and open tubular capillary electrochromatography with carbon nanotubes as stationary phase for the determination of low concentration of illicit drugs in horse urine - Stege, Patricia Wanda (2011)
In this study we developed an interesting alternative to HPLC-mass spectrometry for the quantification of seven important drugs of abuse in racehorses. The procedure proposed in this work is a combination of single-drop microextraction (SDME) and an open tubular capillary electrochromatography (OT-CEC) using multi-wall carbon nanotubes (MWCTs) immobilized into a fused-silica capillary as a stationary phase. The SDME showed to be a powerful tool for extraction/preconcentration of the seven drugs analyzed in the study, showing an enrichment factor between 38- and 102-fold depending on the drug. We have investigated the electrophoretic features of MWCTs immobilized fused-silica capillary by covalent modification of the inner surface of the capillary. The results show a good run-to-run, day-to-day and capillary-to-capillary reproducibility of the method. Compared with the capillary zone electrophoresis (CZE), the coating of the capillary allowed the separation of the analytes with high resolution, with less band-broadening and without distortion of the baseline. The interactions between the analytes and the MWCTs resulted in an increased migration time and probably this was the reason of the front tailing effect. The results showed a good capillary efficiencies and an improved of the electrophoretic separation. © 2011 Elsevier B.V. All rights reserved.